2020
DOI: 10.3390/w12071866
|View full text |Cite
|
Sign up to set email alerts
|

Measuring the Transaction Costs of Historical Shifts to Informal Drought Management Institutions in Italy

Abstract: Coase shows how costly resources are (re)allocated via costly institutions, and that transaction costs must therefore be positive. However, Coase did not elaborate on transitions between institutions which incur positive transaction costs that are characterized by numerous institutional complementarities; that is, feedback loops that inform the need for, and pathways toward, institutional change. Economic investigations of complementary modes of (re)allocation are rarely undertaken, let alone studies o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 37 publications
0
5
0
Order By: Relevance
“…This may be because CAC and market-based policies are more suitable for industrial regions or developed countries, such as China and the USA [27,35,48]. In Italy, CAC is preferable to market-based approaches because the latter require state intervention in resource and sanction management [69]. Previous studies tended to support market-based policies or CAC more than the institutional approach because they often as-sociated institutional processes (political, administrative, and legal) with higher transaction costs [69].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This may be because CAC and market-based policies are more suitable for industrial regions or developed countries, such as China and the USA [27,35,48]. In Italy, CAC is preferable to market-based approaches because the latter require state intervention in resource and sanction management [69]. Previous studies tended to support market-based policies or CAC more than the institutional approach because they often as-sociated institutional processes (political, administrative, and legal) with higher transaction costs [69].…”
Section: Discussionmentioning
confidence: 99%
“…In Italy, CAC is preferable to market-based approaches because the latter require state intervention in resource and sanction management [69]. Previous studies tended to support market-based policies or CAC more than the institutional approach because they often as-sociated institutional processes (political, administrative, and legal) with higher transaction costs [69]. In China, Tang et al [49] noted that the impact of instruments, such as the TDP, highly depends on market perfection, pointing out that as institutional transaction costs increase, innovation and its effects decrease.…”
Section: Discussionmentioning
confidence: 99%
“…Ref. [78] assessed the costs of transitioning drought management institutions in Italy toward informal, participatory and consensus-based approaches during several recent drought events. The work analyzed the allocation of water abstraction licences in the Po basin and concluded that there is an over-allocation of such licences.…”
Section: Drought Management Strategiesmentioning
confidence: 99%
“…Some studies use their analyses to define a set of tools aimed at building more resilient governance systems and institutions or developing innovative adaptation strategies for future drought events (Du et al, 2018 ; Hurlbert & Gupta, 2019 ; King‐Okumu et al, 2018 ; Lordkipanidze et al, 2015 ; Nguyen et al, 2021 ; Sousa Júnior et al, 2016 ; Sullivan et al, 2019 ; Vignola et al, 2018 ). Other studies devote their effort to design novel analytical frameworks that support policy making alongside natural resources or risk managements practices (Bettini et al, 2013 ; Habiba et al, 2011 ; Harou et al, 2010 ; Hund et al, 2018 ; Loch et al, 2020 ; Yates et al, 2013 ).…”
Section: From Impacts To Recovery? Social Resilience and Adaptation T...mentioning
confidence: 99%